Interface-specific mode of protonation–deprotonation reactions underlies the cathodic modulation of fluorescence protein emission. (30th November 2020) - Farha, Trisha Diba; Kim, Samyoung; Hama, Kohsuke; Imayasu, Mieko; Hiratsuka, Yuichi; Miyawaki, Atsushi; Tsutsui, Hidekazu
Abstract: While fluorescence protein immobilized at the metal–solution interface has been known to exhibit voltage-dependent fluorescence, the underlying mechanism has remained unresolved. Here, we addressed the cathodic mechanism employing the characteristic properties of three different fluorescence proteins showing conventional pH-sensitivity, inverse pH-sensitivity, and green-to-red photo-convertibility. Through the analysis, we found that the interface-specific mode of protonation–deprotonation reactions underlies the cathodic effect, where the protonation state is directly coupled to hydrogen evolution at the interface rather than to the environmental acid-base equilibrium. The potential applications based on the interface effect are then discussed, including the spatially-resolved monitoring of hydrogen evolution reactions.